PENAFSIRAN PASAL-PASAL MAKAR TERHADAP KASUS-KASUS POLITIK DI ERA PRESIDEN JOKO WIDODO - Syahra Syahra; Erdianto Effendi; Elmayanti Elmayanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Makar is a form of attack or resistance against a legitimate government with a view to overthrowing the government or opposing a policy that has been determined by breaking the law, either through weapons or other forces or in other ways. In theory, a plot known to the public is a plot shown in a country that can be divided into three parts, namely the plot towards the safety of the President and Vice President, to the territory of the State, as well as to the government. These three actions are regulated in Chapter I of Book II of the Criminal Code on Crimes against State Security, namely Article 104, Article 106, and Article 107.This research uses library research method. This research was conducted by examining the laws, documents and literature relating to the research material. The research approach used in this research is descriptive analysis, which uses research on legal systematics and examines existing norms in criminal law and criminal law regulations, especially the Criminal Code (KUHP) and Law Number 27 of 1999 concerning amendments to the Criminal Code relating to Crimes Against State Security, then the data will be analyzed based on normative-juridical.The results of this study indicate that treason crime is a very dangerous form of crime and is also categorized as a political crime that has characteristics of motives and objectives that are different from ordinary crime and threatened with severe criminal sanctions. a. related to whether the appropriation of the use of Article treason against State security is applied to the suspects is treason offense is an incomplete trial offense related to the security of the State concerning the safety of the president and vice president, rebelling against the legitimate government and sovereignty of the country's territory. b) the allegation of treason committed by police investigators is a form of premium remedium that makes positive law in the Criminal Code as part of protecting the legal interests of the community and the interests of the country's law. In carrying out their role as investigators, the police play an active role in conducting investigations of treason crimes. The police in their role of investigating treason crimes refers to the Criminal Code. Related to the authority of the police to investigate a crime is regulated by the Criminal Procedure Code and the Police Law. In addition, in this case the investigator must understand what is suspected of the suspect in bringing down the treason case. in addition to understanding the offense treason investigators must also be able to prevent the occurrence of a crime of treason.Keywords: Interpretation, Makar Article, Political Case diera President Joko Widodo